Rapid chemical detection and segmentation of latent fingerprints by means of a novel middle-infrared scanning method - Marwick, Björn van; Kümmel, Tim; Wühler, Felix; Lauer, Felix; Hoffmann, Jan; Rädle, Matthias (The analyst, 2024)
The fast and reliable detection, segmentation and visualization of latent fingerprints are the main tasks in forensics. Currently, conventional fingerprints are searched for, recorded and subsequently analyzed via traditional destructive physical and chemical methods. For firmly defined crime objects and undefined crime scenes, the forensic process is very time-consuming and can take several hours for a single fingerprint. In this context, a laser-based measurement technique that records complete latent fingerprints under fifteen seconds in a non-destructive manner was developed that digitizes the fingerprint for postprocessing steps. The optical system is based on confocal measurements in the mid-infrared wavelength range (2 μm-4 μm) to analyze specific chemical substances at crime scenes. The resulting chemical segmentation allows molecule-dependent analysis of latent and visually invisible fingerprints, providing clear conclusions about the perpetrator or the course of the crime. In this study, the application of the developed measurement system (MIR scanner) to capture fingerprints in a molecule-dependent manner within few seconds is demonstrated, compared with reference methods such as FTIR (Fourier transform infrared spectroscopy) imaging, and extended to real crime objects.
Gesehen am 13.05.2025